LINKING VERB ANALYSIS IN EARTH NOVEL BY TERE LIYE (Karya Ilmiah Mahasiswa (KIMA), 2023)
This thesis aimed to determine and identify the types and the use of linking verb. The method of this thesis uses descriptive qualitative and uses note taking as the way in collecting data by reading the novel. Data were taken from Earth novel by Tere Liye. There are types of linking verb found such as Linking verb to-be (am, is, are, was, were, has been, had been) and Linking verb non to-be (look, become, seem, smell, feel). Finally, based on research, it can be concluded there are 497 linking verbs contained in Earth novel, 452 linking verb to-be and 45 linking verb non to-be.